44. INVESTIGATION OF ACUTE KIDNEY INJURY IN SEPSIS PATIENTS AT THE DEPARTMENT OF INFECTIOUS DISEASES IN THE MILITARY HOSPITAL 103 IN 2022 (Vietnam Journal of Community Medicine, 2024)
Objectives: Determine the incidence, stage and risk factors of acute kidney injury (AKI) in sepsis patients in the Military Hospital 103 in 2022. Subjects and research methods: A cross-sectional descriptive study on 86 sepsis patients hospitalized at the Department of Infectious Diseases in the Military Hospital 103 from 11/2021 to 12/2022. Results: The rate of AKI in sepsis patients accounted for 41.9%; the majority of stage I was 55.6%; stage III accounted for the lowest rate of 13.8%. Factors with prognostic significance to the risk of acute kidney injury in sepsis patients: SOFA score ≥ 5 points (OR = 4.83; CI95% 1.91 - 12.18, p < 0.01); Vasopressors used for hypotension (OR = 3.31; CI95% 1.32 – 8.29, p < 0.01); Procalcitonin ≥ 10 ng/ml (OR = 3.18; CI95% 1.28 -7.90, p < 0.05); Arterial blood lactate ≥ 5 mmol/l (OR = 2.76; CI95% 1.02 -7.51, p < 0.05). Conclusion: Acute kidney injury was a common complication in patients with sepsis. High SOFA score, use of vasoactive drugs, increased procalcitonin and high blood lactate were risk factors predicting AKI in patients with sepsis.
Keywords: Acute kidney injury (AKI), sepsis, the incidence, risk factors.